The effect of syllable-level hyphenation on reading comprehension: Evidence from eye movements - Häikiö Tuomo; Heikkilä Timo T.; Kaakinen Johanna K. (American Psychological Association, 2022)
Syllabification by hyphens (e.g., hy-phen-a-tion) is a standard procedure in early Finnish reading instruction. However, recent findings indicate that hyphenation slows down children’s reading already during the first grade (Häikiö, Hyönä, & Bertram, 2015, 2016). In the present study, it was examined whether this slowdown is indicative of deeper processing and/or more strategic reading. To this end, 2nd grade children (N = 36) read short expository and narrative stories while their eye movements were registered. The presence of syllable boundary cue (SBC) was manipulated; for half of the stories, each word was hyphenated at syllable boundaries whereas the other half included no hyphenation. After each story, story comprehension (SC) was measured by three types of oral questions, namely free recall, cued recall, and true/false questions. With regard to reading behavior, SBC interacted with independently measured reading comprehension scores for both forward and regressive fixation times during first pass sentence reading. Hyphenation slowed down reading of good comprehenders to a larger extent than weaker comprehenders in comparison to nonhyphenated condition, especially for regressive fixation times. With respect to SC, cued recall scores were lower in the hyphenated than in the nonhyphenated condition. There was no effect of SBC in free recall or true/false questions. Hyphenation seems to promote phonological encoding even when readers might want to access words via orthographic codes, which are obscured by hyphenation, especially at the whole-word level. This more piecemeal reading style then makes it harder to integrate the pieces into a bigger whole, affecting not only reading speed but also reading comprehension. (PsycINFO Database Record (c) 2018 APA, all rights reserved)